Ofício da carpintaria de móveis em Itabaiana/SE : trabalho, movimento e permanência - Santos, João Pedro Celestino dos (2021)
The world of work in the 21st Century is characterized by the permanent worker submission, by the precarious conditions, low salaries, long working hours, informality and losses of rights conquered through struggles. It is also characterized by the neo liberal ideology of individualizing the subject and the creation of the illusion of being his own boss. Immersed in this world of work are the traditional mechanical crafts which are captured in the capitalist production mood, in its nuances, its technical abilities, its practical knowledge. Among these crafts is the carpentry which remains as an artisanal activity, however it presents the dynamism and changes that are determined by the logic of capitalist industrial production. The carpentry holds a relevant role in the spatial production of the country and of the city, a component of the social relations historically produced. It is present in the municipality of Itabaiana, a benchmark of furniture production in Sergipe, both in relation to the artisanal manufacture and in relation to industrialized production of furniture. The carpentry craft followed the territorial formation of Sergipe in the manufacture of tools for civil construction and furniture. Its temporo-spatial existence results from the development of its own activity and the importance of the furniture as a useful good and a commodity that gets valued in the market. The research ahd as objective to analyse the furniture carpentry craft through the changes in the world of work and the specialized furniture production in Itabaiana, Sergipe. The investigation set out from the questioning about the continuity of the carpentry craft, even with capital action metamorphing the labor, enhancing techniques and propelling the development of new production technologies. The carpentry reality investigation in Itabaiana, Sergipe was reasoned in Historical and Dialectical Materialism, method that allows the social practical analysis in its concreteness and historical and social determinations. Anchored on the interpretation method, the methodological procedures to the study of the concrete reality were the qualitative research which allows the meeting with the subjects involved in the carpentry manufacture and interviews were made, questionnaires were applied and photography register, in addition to research in secondary sources which exhibited the reality. The empiric investigation, reasoned by the historical dialectical materialism led to exhibit the continuity of this craft in contemporaneity. The carpentry subsists, but it is guided by the capitalist relations of production which imposed the reconfiguration of the techniques, substitution of the hand tool by machines, usage of new technological mechanisms like the reconstituted wood panels in the confection of furniture. Besides that, the carpenter is not the only producer anymore, there are also the workers who live from the furniture production as a job, without practical knowledge historically accumulated.